The Effect of Canva-Based Learning Media on Students’ Learning Motivation in Islamic Religious Education at Junior High School: Pengaruh Media pembelajaran berbasis Canva terhadap Motivasi Belajar Pendidikan Agama Islam Siswa Sekolah Menengah Pertama - Idhar Idhar; Ilyas Ilyas; Arif Rahman (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2025)
This study aims to analyze the effect of using Canva media on students’ learning motivation in Islamic Religious Education (IRE) at SMP Negeri 2 Dompu. The low level of students’ enthusiasm in IRE learning, which is still dominated by conventional methods, encourages the use of more innovative digital visual media. This study employed a quantitative ex post facto approach. The population consisted of 143 eighth-grade students, with 23 students selected as the sample through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS version 25. The results showed that the use of Canva media had a significant effect on students’ learning motivation in IRE (t = 6.372; p < 0.05), with a coefficient of determination (R²) of 0.621. These findings indicate that Canva media is effective in increasing students’ interest, attention, and engagement in IRE learning. Therefore, the use of Canva is recommended as a creative and contextual learning medium in line with the Merdeka Curriculum.